IMPLEMENTASI GREEN HOSPITAL PADA PEMBANGUNAN RUMAH SAKIT UMUM KABUPATEN KARAWANG - Agung Aditia Pratama Aditia Pratama; Iskandar Muda Purwaamijaya; Rina Marina Masri (Universitas Pendidikan Indonesia (UPI), 2021)
Green Hospital is a concept that is believed to reduce the effects of global warming. Therefore, hospital buildings should apply the concept of an environmentally friendly hospital (Green Hospital). In the construction of the Permata Keluarga Karawang Hospital, there are several subindicators of the Green Hospital that have not been accommodated. Problem solving can be done by the hospital by improving several sub-indicators and applying subindicators that are not yet available. The purpose of this study was to review and conduct a thorough evaluation in the environmental, financial and technical scope of the implementation of Green Hospital in the construction of the Permata Keluarga Karawang Hospital, as well as to provide solutions to the sub indicators of the Green Hospital that were not appropriate.Keywords: Building Construction, Green Hospital, Hosptal, Implementation